Changes in the adult sex ratio of six duck species breeding populations over two decades - Monika Homolková; Petr Musil; Diego Pavón-Jordán; Dorota Gajdošová; Zuzana Musilová; Šárka Neužilová; Jan Zouhar (Avian Research)
Despite all efforts, long-term changes in the adult sex ratios of breeding duck populations are still unclear; this uncertainty is especially true for male-bias populations, which are often under the scrutiny of researchers lacking convenient results for the active protection of endangered species. Species with male-bias populations are usually strongly affected by a decline in population size that leads to a higher extinction risk. In this study, we examined our long-term data of the abundance of breeding populations in six duck species (Mallard Anas platyrhynchos, Gadwall Mareca strepera, Red-crested Pochard Netta rufina, Common Pochard Aythya ferina, Tufted Duck Aythya fuligula, and Common Goldeneye Bucephala clangula) from fishponds in South Bohemia, Czechia, between 2004 and 2022. This evidence was used to assess long-term changes in the adult sex ratio in these breeding populations and investigate the possible effects of the NAO index (North Atlantic Oscillation index) on them, indicating climate conditions in winter. We determined a long-term decrease of the proportion of females in the breeding season in two of the six examined species: Common Pochard and Red-crested Pochard, which is driven by the long-term increase in the number of males in contrast to the decreasing or stable number of females likely caused by different migration behaviours between females and males. In the case of Common Pochard, in breeding populations, we estimated 60–65% of males in the early 2000s rising to 75–80% in the early 2020s. However, we establish no significant effects linked to climate conditions of the previous winter in these species as a crucial cause of the changes of the proportion of females in the breeding population.